Hybrid resonant three‐level ZCS converter suitable for photovoltaic power MVDC distribution network. Issue 11 (21st July 2020) - Azeem, Syed Waqar; Tariq, Irfan; Mehmood, Kashif; Ehab, Muhammad; Rizwan, Mian; Mond, Muhammad Asim
Abstract : This study presents a hybrid resonant three‐level (TL) zero‐current‐switching (ZCS) converter for distributed photovoltaic power applications accessing medium‐voltage DC (MVDC) distribution network. The main constituents of the converter is a neutral point clamped TL circuit, an auxiliary circuit along with two transformers and six switches. The ZCS condition of the TL circuit is reached by operating the auxiliary circuit utilising pulse width modulation technique. It delivers the majority of the power and the switching loss is remarkably reduced. A section on the influence of the turn's ratio of the auxiliary transformer on the current is also presented. The piecewise linear electrical circuit simulation simulation results validate the designed parameter principles. For the sake of comparison, an experimental prototype is developed of 300–1500 V/1500 W to validate the performance of the proposed converter.